Large Group Exposure Treatment: A Feasibility Study of Exposure Combined with Diaphragmatic Breathing in Highly Dental Fearful Individuals - Wannemueller, André; Jöhren, Hans-Peter; Borgstädt, Alina; Bosch, Jessica; Meyers, Milena; Völse, Miriam; Scholten, Saskia; Margraf, Jürgen (Frontiers in Psychology, 2017)
A large-group one session treatment (LG-OST) combining exposure and diaphragmatic breathing as a bodily coping element was carried out to investigate its feasibility and effectiveness in a sample of 43 highly dental fearful individuals treated simultaneously. We assessed subjective dental fear, dysfunctional dental-related beliefs and perceived control pre- and post-intervention and at four-month follow-up. Participants additionally performed a behavioural approach test (BAT) pre- and post-intervention. During the applied exposure exercises, four participants (9.3 %) discontinued the program all reporting too high levels of distress. Regarding subjective dental fear and dysfunctional dental related beliefs post treatment effects, LG-OST showed medium to large effect sizes, ranging from Cohen’s d = .51 to d = .84 in the Intention-to-Treat analysis. Subjective dental fear improved clinically significantly in about one fourth (25.6 %) of therapy completers. All post-treatment effects remained stable over time. Concerning the behavioural fear dimension, we observed a strong ceiling effect. Already at pre-assessment, participants accomplished more than six out of seven BAT-steps. Thus, behavioural approach did not increase significantly following treatment. Overall, the LG-OST protocol proved feasible and efficient. Compared to other one-session individual and multi-session group treatments the observed LG-OST effects were smaller. However, if LG-OST could match the efficacy of highly intensive short treatments delivered in an individual setting in the future, for example, by applying a wider array of exposure exercises, it could be a very useful treatment option as an intermediate step within a stepped care approach.